The Image Of A Man In The English And Russian Paroemiological World Pictures - Ravilevna Shaimardanova, Milyausha (2017)
Paroemias constitute an extremely important language layer in the field of gender perspective investigation which helps identify various gender stereotypes of different peoples. This article is devoted to the gender issues in English and Russian paroemiological world pictures, images and assessments correlated to a man, and the semantic areas where they are most prevalent. The main methods of a research are common-language methods: method of scientific observation, comparative and contrastive method, descriptive method. Based on studies of English and Russian proverbs and sayings which reflect the gender stereotypes of the compared ethnic groups, the authors try to create man’s image in each socio-cultural environment and to reveal their common and specific characteristics. Analysis of empirical material allows drawing the following conclusion: portraits of the English and Russian men in the considered PWP differ considerably. One of the main components of an image of the English man is the set of the rules shown to him. For the English man except worthy behavior and inner world the large role is played by welfare and appearance.